Infrapatellar fat pad of patients with end-stage osteoarthritis inhibits catabolic mediators in cartilage. Issue 2 (13th October 2011) - Bastiaansen-Jenniskens, Yvonne M; Clockaerts, Stefan; Feijt, Carola; Zuurmond, Anne-Marie; Stojanovic-Susulic, Vedrana; Bridts, Chris; de Clerck, Luc; DeGroot, Jeroen; Verhaar, Jan AN; Kloppenburg, Margreet; van Osch, Gerjo JVM
Abstract : Objective: Adipose tissue is known to release inflammatory cytokines and growth factors. In this exploratory study, the authors examined whether the infrapatellar fat pad (IPFP) closely located to cartilage in the knee joint can affect cartilage metabolism. In addition, the authors analysed whether the macrophage types present in IPFP could explain the effect on cartilage. Methods: IPFP explants obtained during total knee replacement of 29 patients with osteoarthritis (OA) were used to make fat-conditioned medium (FCM). Explants of bovine cartilage were cultured with or without FCM. Nitric oxide (NO) and glycosaminoglycan release and gene expression of matrix-degrading enzymes in cartilage were analysed. To stimulate catabolic processes in the cartilage, the authors added interleukin 1β, and the effect of six FCMs was evaluated. The presence of different types of macrophages (CD68+, CD86+ and CD206+) in OA IPFPs was compared with subcutaneous adipose tissue samples and IPFP samples from patients with an anterior cruciate ligament rupture. Results: FCM alone reduced NO and glycosaminoglycan release and matrix metalloproteinase (MMP)1 gene expression by the cartilage. Moreover, when catabolic conditions were enhanced with interleukin 1β, FCM inhibited NO production as well as MMP1 and MMP3 gene expression and increased collagen type II gene expression. Significantly more CD206+ cells were present in OA IPFP samples than in subcutaneous fat or anterior cruciate ligament IPFP samples. Conclusion: In contrast to the authors' expectations, medium conditioned by end-stage OA IPFP inhibited catabolic processes in cartilage. CD206+ cells present in the IPFPs used for making the FCM might have contributed to the inhibition of catabolic processes in the cartilage.